BIODEGRADATION OF GLYPHOSATE CONTAINING HERBICIDE BY SOIL FUNGI - Omorinola, Alake A; Ogunbiyi , Oluwagbenga J; Jegede, Rotimi J; Adeleke, Maryam A; Fakolade, Benjamin A (Innovare Journal of Life Sciences, 2023)
Ten fungal isolates were isolated from two herbicide-contaminated soil farms obtained from Amoyo and the University of Ilorin environment in Kwara State after enrichment with mineral salt medium (MSM) supplemented with glyphosate-containing herbicide. The growth of fungal isolates was efficiently stimulated by the organophosphorus herbicide. Fungi isolated were subjected to screening by varying the herbicide concentrations from 0.1 to 3%, which is prepared with MSM. This screening showed that all the fungal isolates had the ability to act in the biodegradation process. However, varying degradative potentials were observed, as some had heavy growth while others had only slight or no growth as the concentrations of the herbicide increased. The ten fungal isolates were characterized and identified as Aspergillus niger, Penicillum spinulosum, Aspergillus terrus, Aspergillus flavus, Fusarium oxysporum, Mucor spp., Aspergillus oryzae, Aspergillus tamari, Rhizopus stolonifer, and Trichoderma koningii, and these were reduced to six after screening with 3% concentration of the herbicide. Four isolates (A. niger, F. oxysporum, Mucor spp., and A. flavus) were selected based on their growth ability on the medium during screening and were used in the biodegradation study. However, there is an increase in fungal dry weights ranging from 8.60 to 18% for 12 days. This shows that these fungi can be employed in the biodegradation of herbicides since they are potentially effective species and are environmentally safer alternative to protect the soil from the contamination of glyphosate-containing herbicide residues.